KONTRUKSI SOSIAL TRADISI “OMAH PITU” DUKUH SITUMPENG DALAM PERSPEKTIF PARADIGMA DAKWAH KULTURAL - Ahmad Hidayatullah; Wirayudha Pramana Bhakti (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2020)
Traditions in a society have important roles in determining the direction and social destination in society itself. When a tradition still relevants and still used by people, the tradition will be maintained at the same time, and also vice versa. If it can not give the benefits for people, it will be leaved. As in Situmpeng viileage, Pesalakan, Bandar, Batang City. After many years, “Omah Pitu” that bequethed by their ancestors, still exist until now. Of course includes many problems happen inside. Using kind of qualitative research with phenomenological approachment as a technic of analysis, this research try to understand about how social crosntructions of Situmpeng’s poeple to “Omah Pitu” in the context of cultural dakwah paradigm. As a result of the research can be cpncluded that nowdays “Omah Pitu” only seven houses thal still exist in Situmpeng. This suitable with the name of this village from the word “Situ” and “Lempeng” that have meaning “omahe pitu lempeng” (only seven houses). The social constructions in this society to the tradition “Omah Pitu” -like L Berger theory- devided into four steps, there are constructions, maitenance, repairs, and changes. Those steps veri dinamic and born “Omah Pitu” that still exist in Situmpeng with some adaptations that done by society with follow the times change. As non-habitable buildings, the concept of two houses that have a gutter,etc. Nevertheless if looked from that theory, the last step, change, it is not fully happened because there is no “radical” change that get rid of the old values. Besides it, “Omah Pitu” that still sustainable in Situmpeng can still exists because it got a legitimation of Islamic rules that followed by Situmpeng’ people. It means that the diversity in Situmpeng which entered in Cultural Dakwah Paradigm causes this tradition doesn’t need to be confronted srictly as when faced with Islam in Purritans ways.